Implementation of HCV screening in the 1969–1989 birth‐cohort undergoing COVID‐19 vaccination. (12th March 2022) - D'Ambrosio, Roberta; Rizzardini, Giuliano; Puoti, Massimo; Fagiuoli, Stefano; Anolli, Maria Paola; Gabiati, Claudia; D'Amico, Federico; Pasulo, Luisa; Restelli, Umberto; Colombo, Massimo; Lampertico, Pietro
Abstract: Background and Aim: The World Health Organization (WHO) goal of hepatitis C virus (HCV) elimination by 2030 relies on the scaling‐up of both identification and linkage to care of the infected population, worldwide. In Italy, the estimated burden of HCV carriers who are unaware of their infection amounts to 200 000 persons, a projection that reinforces the need for broadening population access to effective screening programmes. Methods: A pivotal screening programme targeting subjects born between 1969 and 1989 has been conducted in Lombardy, Northern Italy, where point‐of‐care (POC) testing was offered for free concomitantly to COVID‐19 vaccination. Results: Amongst 7219 subjects born between 1969 and 1989 who underwent HCV screening through POC, 7 (0.10%) subjects tested anti‐HCV positive: 5 (0.07%) had confirmed anti‐HCV positivity (Table 1) and 4 of them (0.05%) were HCV‐RNA positive by standard confirmation tests. Conclusions: This pivotal study demonstrated the feasibility of a POC‐based anti‐HCV screening programme in young adults undergoing COVID‐19 vaccination. The prevalence of HCV infection in subjects born in the 1969–1989 cohort in Italy seems to be lower than previously estimated. Whether the extension of this programme to subjects born before 1969 could lead to improved screening effectiveness should be a matter of debate.